2001
DOI: 10.1007/s004300100066
|View full text |Cite
|
Sign up to set email alerts
|

Nramp1 gene affects selective early steps in macrophage-mediated anti-cryptococcal defense

Abstract: Cryptococcus neoformans is an opportunistic fungus responsible for severe and often recurrent meningoencephalitis in immunodepressed patients. Initial evidence suggests that C. neoformans is a facultative intracellular pathogen; however, the strategies by which C. neoformans undergoes survival and eventually proliferation have not been elucidated. We investigated the role of Nrampl gene in macrophage-mediated anti-cryptococcal defense. Using cell lines expressing the functional, mutated or knockout gene, it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…IL-12 is crucial in the development of an effective immune response, favouring protective Th1-dependent resistance (Trinchieri, 1997). Moreover, we (Blasi et al, 2001a) and other authors (Kawakami et al, 1999) have shown that Cn can inhibit IL-12 production, whereas, as said above, HHV-6 can induce its production. In this work, we found that THP1/JJHAN HHV-6 produced higher amounts of IL-12 and IFN-a with respect to the control cultures in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…IL-12 is crucial in the development of an effective immune response, favouring protective Th1-dependent resistance (Trinchieri, 1997). Moreover, we (Blasi et al, 2001a) and other authors (Kawakami et al, 1999) have shown that Cn can inhibit IL-12 production, whereas, as said above, HHV-6 can induce its production. In this work, we found that THP1/JJHAN HHV-6 produced higher amounts of IL-12 and IFN-a with respect to the control cultures in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 69%
“…Different mechanisms allow Cn to avoid macrophage-mediated defences, significantly impairing Cn ingestion and/or enhancing intramacrophage survival and replication of the pathogen (Tucker & Casadevall, 2002;Levitz, 2001). In addition, Cn can alter the cytokine secretory response of macrophages (Blasi et al, 1995(Blasi et al, , 2001aKawakami et al, 2000;Goldman et al, 2001;Mucci et al, 2003;Uicker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that macrophage cell lines derived from BALB/c mice such as J774 contain defects in the membrane transporter NRamp, which is required for wild‐type oxidative burst (Barton et al ., 1995) and is involved in anticryptococcal killing (Blasi et al ., 2001). Thus, it may be less likely for an oxidative killing mechanism to be primarily responsible for the rapid demise of the vps41 Δ strain in this cell line, and, indeed, the vps41 Δ mutant in vitro did not appear to show altered survival in response to oxidative stresses such as hydrogen peroxide or menadione, previously shown to be fungicidal for C. neoformans (Narasipura et al ., 2003; de Jesus‐Berrios et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro established microglial cell‐line BV2 [25] is available and retains the morphological, phenotypical and functional properties described for freshly isolated microglial cells [26]. In particular, BV‐2 cells exert constitutive and IFNγ‐enhanced anticryptococcal effects via fungal ingestion and nitric oxide production [27–29]. On the other hand, cryptococcal capsule formation and melanization have been described as escape mechanisms by which C. neoformans overcomes host defences and particularly microglial cells [30–33].…”
Section: Introductionmentioning
confidence: 99%